LA EXPRESIÓN DEL LAMENTO EN LA EPISTOLOGRAFÍA GRIEGA DE TEMA ERÓTICO A LA LUZ DE LAS TEORÍAS RETÓRICAS GRIEGAS: LAS CARTAS DE ALCIFRÓN - Vicente Sánchez, Ana (Myrtia, 2008)
The expression of the lament in erotic Greek epistolography from the perspective of rhetorical Greek theories: Alciphron’s Letters'. A study about the way to express lament or complaint in Alciphron’s Letters and its relationship with rhetorical Greek prescriptions.